Dysregulated coagulation associated with hypofibrinogenaemia and plasma hypercoagulability: Implications for identifying coagulopathic mechanisms in humans - Marchi, Rita; Walton, Bethany L.; McGary, Colleen S.; Lin, Feng-Chang; Ma, Alice D.; Pawlinski, Rafal; Mackman, Nigel; Campbell, Robert A.; Di Paola, Jorge; Wolberg, Alisa S. (Thrombosis and Haemostasis, 2012)
Identifying coagulation abnormalities in patients with combined bleeding and thrombosis history is clinically challenging. Our goal was to probe the complexity of dysregulated coagulation in humans by characterizing pathophysiologic mechanisms in a patient with both bleeding and thrombosis. The patient is a 56-year-old female with a history of haematomas, poor wound healing, and thrombosis (retinal artery occlusion and transient cerebral ischaemia). She had a normal activated partial thromboplastin time, prolonged thrombin and reptilase times, and decreased functional and antigenic fibrinogen levels, and was initially diagnosed with hypodysfibrinogenaemia. This diagnosis was supported by DNA analysis revealing a novel FGB mutation (c.656A>G) predicting a Q189R mutation in the mature chain that was present in the heterozygote state. However, turbidity analysis showed that purified fibrinogen polymerisation and degradation were indistinguishable from normal, and Bβ chain subpopulations appeared normal by two-dimensional difference in-gel electrophoresis, indicating the mutated chain was not secreted. Interestingly, plasma thrombin generation testing revealed the patient’s thrombin generation was higher than normal and could be attributed to elevated levels of factor VIII (FVIII, 163–225%). Accordingly, in an arterial injury model, hypofibrinogenaemic mice (Fgn+/−) infused with factor VIII demonstrated significantly shorter vessel occlusion times than saline-infused Fgn+/− mice. Together, these data associate the complex bleeding and thrombotic presentation with combined hypofibrinogenaemia plus plasma hypercoagulability. These findings suggest previous cases in which fibrinogen abnormalities have been associated with thrombosis may also be complicated by co-existing plasma hypercoagulability and illustrate the importance of “global” coagulation testing in patients with compound presentations.
Keywords: Thrombin generation; factor VIII; hypofibrinogenaemia; thrombosis; bleeding